2007
DOI: 10.1002/jgm.1037
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus‐mediated gene transfer is attenuated by sodium bicarbonate

Abstract: To our best knowledge, this is the first report unraveling the significance of NaHCO(3) in gene transfer. Our finding suggests that baculovirus-mediated gene transfer can be readily enhanced by omitting NaHCO(3) from the medium during the transduction period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…It has been previously suggested that the HCO 3 − -ion in DMEM inhibits baculoviral transduction by inhibiting the viral endosomal escape or accelerating the routing of baculovirus-containing vesicles to lysosomes for degradation (Shen et al, 2007). However, no exact mechanistic explanations for the observed results have been reported.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…It has been previously suggested that the HCO 3 − -ion in DMEM inhibits baculoviral transduction by inhibiting the viral endosomal escape or accelerating the routing of baculovirus-containing vesicles to lysosomes for degradation (Shen et al, 2007). However, no exact mechanistic explanations for the observed results have been reported.…”
Section: Discussionmentioning
confidence: 68%
“…Previous results suggest that Mg 2+ , Ca 2+ , K + and Na + do not influence the baculovirus transduction (Hsu et al, 2004;Shen et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One key determinant accounting for the improved transduction is the surrounding solution. PBS is free of NaHCO 3 , a common buffering agent in the medium, and is superior to NaHCO 3 -containing DMEM as the surrounding solution with respect to transduction efficiency and transgene expression [14,49] because NaHCO 3 inhibits baculovirus transduction by reducing the intracellular virus number [55]. Owing to the key role of NaHCO 3 , this transduction protocol may be modified by using NaHCO 3 -deficient DMEM in lieu of PBS as the surrounding solution.…”
Section: B Factors Influencing Baculovirus-mediated Expressionmentioning
confidence: 99%